How the Royal Commission Health Services Program in Jubail, Saudi Arabia, is using social media?. (2021) - Hassan, Hanadi; Alhodaib, Hala; Alanezi, Fahad; AlThani, Bashair; Althumairi, Arwa; Alanzi, Turki; Alsalman, Demah; Al-Fayez, Asma; Alameri, Rana
Abstract: Background: Hospitals have used social media to promote health, disseminate health information, communicate with healthcare providers and patients, recruit staff, and advertise health services, among other objectives. Purpose: The objective of this research was to investigate how social media platforms are used by the staff of the Royal Commission Health Services Program in Jubail (RCHSP-J), Saudi Arabia. Materials and methods: A descriptive cross-sectional study was utilized to investigate the use of social media in the RCHPS-J. The study was conducted in two stages. During the first stage, data were collected through online searches to detect the general characteristics of the RCHSP-J and the operation of its website. In the second stage, a mixed (quantitative and qualitative) web-based questionnaire was designed and distributed to the staff of this organization to detect their views on the use of the social media program implemented in this institution. Results: The online search revealed that the RCHSP-J was a secondary general hospital consisting of three primary healthcare centers. The most popular social media used by the participants in the RCHPS-J was Twitter (48%). The respondents considered that social media platforms facilitated communication (23%), helped to disseminate information about medical advances (20%), provided low-cost advertising support (11%), and improved the reputation of the hospital (28%). The participants thought that the main limitations of the social media program at the RCHPS-J were financial restrictions and lack of human resources (17%), limited awareness about the use of the social media program (17%), and concerns about security and privacy issues (46%). Conclusion: The results indicated that the use of social networks in the Royal Commission Health Services Program in Jubail (RCHSP-J) was beneficial from many points of view, but some limitations prevented the effective use of these platforms to promote the delivery of better health services. In this sense, it is necessary to develop a plan aimed to provide the social media program with sufficient financial and human resources and implement a security system to protect the privacy and confidentiality of data. It is also essential to raise awareness of the staff about the importance of social networks in improving communication, social networking, education, dissemination of medical information, and health promotion. The results of this research can help optimize the implementation of social media programs in Saudi Arabian hospitals.